Trend in coordination for integration of medical treatment and disease prevention in the mainland of China, 2004 - 2020: a statistical data based analysis - Wenxin YAN; Xin GUO; Xia LIU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the development of coordination for the integration of medical treatment and disease prevention (treatment-prevention) in 31 provincial level administrative divisions (PLADs) across China during 2004 - 2020 and to provide a reference for promoting the integration of treatment and prevention in Healthy China construction. MethodsBase on the data collected from the China Health Statistical Yearbook and the China Statistical Yearbook of 2004 - 2020, we compiled relevant indicators for measuring comprehensive development of the medical system and the public health system at national level and PLAD level. We conducted a coupling coordination model analysis and an interrupted time series model analysis (ITSA) to test instantaneous and persistent impact of the "New Medical System Reform Policy" on the development, the degree of coupling, and coordination of the treatment-prevention integration subsystem. ResultsFrom 2004 to 2020, the index for comprehensive development of medical system (SY) increased from 0.560 to 0.692 at national level and the SY also increased for all the PLADs with the ranges from 0.385 - 0.655 to 0.524 - 0.758; during the same period, the index for comprehensive development public health system (SG) increased from 0.747 to 0.875 at national level and the SG of all the PLADs increased similarly in the ranges from 0.501 - 0.846 to 0.696 - 0.995. The range-specific SY and SG were the highest for the PLADs in eastern China in 2020, with the ranges of 0.573 - 0.703 for SY and 0.764 - 0.901 for SG. The results of ITSA showed that the "New Medical System Reform Policy" had a significant transient impact (β2 = 0.024 - 0.145, P < 0.05) and persistent impact (β3 = 0.004 - 0.032, P < 0.05) on the development of medical system (SY) in most PLADs, but not on public health system (SG). From 2004 to 2020, the coupling degree (C) of medical system and public health system at national and PLADs level were all above 0.9, indicating a good system coupling. The index (D) for degree of coordination in treatment-prevention integration increased from 0.805 in 2004 to 0.880 in 2020 at national level and the range of D increased from 0.663 - 0.852 in 2004 to 0.777 - 0.930 in 2020 at PLAD level. ConclusionComprehensive development of treatment-prevention integration subsystem in has been improving during 2004 - 2020 in China, and the degree of coupling coordination in treatment-prevention integration has been gradually strengthened, but regional difference still exists.